Accident study for Kuantan town / Gapar Asan and Mohamad Abdul Rahman - Asan, Gapar; Abdul Rahman, Mohamad (1986)
Motor vehicle accident have become a major problem in recent years, causing death, injury and property damage. In order to ascertain the magnitude of the problem in hand, comparison of rates between the national figure and findings of other researches to that of Kuantan is made. The study area, areas under the jurisdiction of Kuantan Municipality incorporate the CBD area as well as radial routes and links. Analysis of one year data (1985) was conducted to investigate the factors in the occurence and examine the characteristics of the accidents. This analysis, in general, zonal and by specific locations, reinforced by suplementary surveys and ingenuity as reported by other researchers are made the basis of recommending improvements. Several recomendations have been forwarded on the expectation that it will influence a reduction in the high rates of accident that are found in Kuantan.